Correlation Analysis of Learning Motivation with Cognitive Physics Learning Outcomes of High School Students on Static Fluids - Fajar Bahari; Subiki Subiki; Lailatul Nuraini (Jurnal Geliga Sains: Jurnal Pendidikan Fisika, 2023)
Physics is a branch of science that studies natural phenomena and phenomena. Learning physics is often considered difficult by students. This thinking can affect the results of student physics learning. This research purpose was to examine the relationship between students' motivation to learn physics and the physics learning outcomes of high school students on the subject of static fluid. The research method used is correlational quantitative. The sample for this research was students of class XI MIPA 4 at SMAN 1 Gedeg, Mojokerto Regency, which were determined using a purposive sampling area technique. Data collection was carried out by distributing questionnaires for students' motivation to learn physics with the ARCS indicator, while data collection on learning outcomes was carried out by means of a posttest. The analysis technique used in this study is descriptive statistical analysis and Pearson correlation analysis. The results showed that the average student’s motivation to learn physics was 3.49 and the students' physics learning outcomes were 67.34. The results of the Pearson correlation test obtained a value of Sig. (2-tailed) of 0.025 which means there is a correlation between variables. Based on these results, it can be concluded that there is a correlation relationship between students' physics learning motivation and student physics learning outcomes on the subject of static fluid. The Pearson Correlation value of 0.395 which is in the interval from 0.21 to 0.40 indicates a weak level of relationship between students' motivation to learn physics and students' physics learning outcomes.